Kerangka Berfikir Penelitian Kuantitatif - Fallenia, Fay Della; Syafitri, Ramadani; Syahputri, Addini Zahra (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
It was explained that the framework of thinking is the rationale that contains a combination of theory and facts, observations, and literature review, which will be used as the basis for research activities. In this definition, the framework of thinking is made more identical to scientific writing. Usually it has started to be prepared before carrying out research activities which contain all the research variables to be carried out. the meaning of thinking can then be explained or described in the form of an interconnected arrangement of charts, or flowcharts. So that from different sources, the framework is defined as a diagram that outlines the logical flow of a study. So that the frame of mind is basically compiling all variables or everything that will later help carry out research properly and correctly. Meanwhile, in general writing, such as non-scientific writing. Make think contains the flow of all the problems that will be told in the written work that is made. Starting from the search, then the cause of the conflict, then the conflict resolution process, and the ending or closing. Everything is listed in the frame of mind.